Analisis Ketahanan Keuangan Lembaga Pendidikan Non-Profit Berbasis Perspektif Keuangan Balanced Scorecard : Studi Kasus Mts Intisyarul Ulum Kota Probolinggo - Yulia Nurhanasah (CV. ITTC INDONESIA, 2026)
Financial resilience is a crucial element in ensuring the sustainability of non-profit educational institutions, particularly madrasahs that rely heavily on government funding and community contributions. This study aims to analyze the financial resilience of MTs Intisyarul Ulum Kota Probolinggo using the financial perspective of the Balanced Scorecard as an evaluative framework. This research employed a qualitative case-study approach, with data collected through in-depth interviews, field observations, and an examination of financial documents from 2022, 2023, and 2024. The results indicate that institutional revenue increased each year, expenditures were managed efficiently, and liquidity remained stable, allowing operational activities to run smoothly. Interview findings reinforce that priority-based budgeting and cost-control strategies play an essential role in maintaining financial stability. The discussion shows that the institution has implemented several principles of the Balanced Scorecard effectively despite challenges related to limited income diversification and the absence of long-term financial planning. In conclusion, the institution’s financial resilience is categorized as sufficiently stable, although further strategic strengthening is needed to ensure long-term sustainability.